Assessment of Gait Ability of Subjects With Chronic Ankle Instability During an Inter-trial Variability Gait Task According to Changes in Gait Speed - Kwon, Jeonghan; Choi, Jongduk (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2023)
Background: Ankle sprains occur frequently among humans who undertake various body movements. Diverse walking environments and dual tasks, that can affect ankle sprains, have been studied. However, there is a lack of research on inter-trial variability according to the changes in gait speed. Objects: The purpose of this study was to compare the adaptive ability of walking between the subjects with chronic ankle instability and healthy adults while performing a walking task with different walking speeds. Methods: In this study, 24 people in the chronic ankle instability group and 24 people in the healthy ankle group were selected as subjects. The length of the pre-measurement and the actual walking measurement were both set to 4.6 m. Once the subjects entered the measurement section, they changed their gait speed according to the randomly assigned speed change. Gait was measured twice and the average value was used for the analysis. Results: The coefficient of variation (CV) of cycle time in subjects with chronic ankle instability showed a significant difference in all cases except when the subjects changed their speed from preferred to slow and from slow to preferred. The CV of step length demonstrated a significant difference in all cases except for the change from slow to preferred and from preferred to fast. The cycle time and step length differential showed a significant difference only when the subjects changed the speed from slow to fast. Conclusion: The subjects with chronic ankle instability were found to have significantly reduced walking adaptability while performing inter-trial variability tasks with different gait speeds compared to healthy subjects.